De cocal em cocal: a atuação do BCD cocais para a promoção da cidadania em São João do Arraial no Piauí - Leal, Mariane Goretti de Sá Bezerra (2021)
The Community development banks (BCDs) are solidary economic ventures considered of social utility for operating in needy territories whose main goal is to promote local development while expanding and strengthening citizenship. At this point, the objective of the research was to understand the contribution of BCDs to the promotion of citizenship in São João do Arraial through the perception of their managers and beneficiaries. This is an exploratory and descriptive study, using a qualitative approach. For data collection, the techniques of documental survey, non-participant observation, as well as semi-structured interviews that were applied to 02 managers and 06 beneficiaries of BCD Cocais were adopted. In data analysis, we used the content analysis approach carried out with the support of the ATLAS.ti software for data organization and codification. The results achieved show that BCD Cocais is configured as a solidary economic enterprise of effective social utility insofar as its actions are aimed at collective benefits that favor, individually or collectively, the community and enable the exercise of citizenship practices in São João of the Arraial. In this sense, through the association matrix between citizenship practices and BCD Cocais social utility actions, it was possible to prove that several citizenship practices are exercised from different social utility actions. Thus, the study made it possible to understand that the social utility actions of BCD Cocais in the socio-environmental, socio-political, socio-cultural, socio-economic and socio-institutional spheres with the beneficiaries is associated with the exercise of civil, political, social and environmental rights and duties that contribute to the expansion of citizenship in São João do Arraial. The association matrix proposed to analyze the relationship between the social usefulness of CDBs and the promotion of citizenship can be considered a theoretical contribution of the research, confirming evidence pointed out in previous studies, as well as contributing to deepen the knowledge on the field of BCDs and the theme of citizenship. From a practical perspective, the research contributes to the improvement of the management actions of the BCDs in order to improve their performance in the territories and, consequently, local development and the strengthening of citizenship. As a social contribution of the study, we can highlight a greater awareness of individuals about the exercise of citizenship in the territory through the BCDs, which may contribute to a greater maturity of the community with a view to achieving citizenship and strengthening the territory.